2020
DOI: 10.1021/jacs.0c05383
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Mediated Bidirectional Control over Carbonic Anhydrase Activity in Cells and in Vivo Using Azobenzenesulfonamides

Abstract: Two azobenzenesulfonamide molecules with thermally stable cis configurations resulting from fluorination of positions ortho to the azo group are reported that can differentially regulate the activity of carbonic anhydrase in the trans and cis configurations. These fluorinated probes each use two distinct visible wavelengths (520 and 410 or 460 nm) for isomerization with high photoconversion efficiency. Correspondingly, the cis isomer of these systems is highly stable and persistent (as evidenced by structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…This compound enables efficient conversion of light energy into chemical energy and displays high quantum yields of photoisomerization [48] . The azobenzene sulfonamide 21 can be isomerized by visible light and it has been exploited in controlling the activity of carbonic anhydrase in cells and in vivo both in the forward and backward directions employing visible light [49] . Supramolecular valves have been constructed using host‐guest interaction of β‐cyclodextrin and tetramethoxy substituted azobenzene [50] .…”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
See 1 more Smart Citation
“…This compound enables efficient conversion of light energy into chemical energy and displays high quantum yields of photoisomerization [48] . The azobenzene sulfonamide 21 can be isomerized by visible light and it has been exploited in controlling the activity of carbonic anhydrase in cells and in vivo both in the forward and backward directions employing visible light [49] . Supramolecular valves have been constructed using host‐guest interaction of β‐cyclodextrin and tetramethoxy substituted azobenzene [50] .…”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
“…[48] The azobenzene sulfonamide 21 can be isomerized by visible light and it has been exploited in controlling the activity of carbonic anhydrase in cells and in vivo both in the forward and backward directions employing visible light. [49] Supramolecular valves have been constructed using host-guest interaction of β-cyclodextrin and tetramethoxy substituted azobenzene. [50] These valves were used to control the release of the drug doxorubicin in deep tissue from mesoporous silica nanoparticles triggered by red light.…”
Section: Azobenzene Derivativesmentioning
confidence: 99%
“…As shown in Figure S4, when the Acr-Azo-SA was exposed to UV light, the absorbance at 345 nm decreased because of the decreased level of the trans form of the Azo unit, and an increase in the absorbance was observed at 440 nm due to the increased level of the cis form. [21] These results suggested that the Azo units could still be isomerized after being incorporated into Acr-Azo-SA. The inhibitory effect of Acr-Azo-SA was then investigated.…”
Section: Resultsmentioning
confidence: 94%
“…For the first time, there is a single nanosystem that enables sustained 1 O 2 generation and sufficient oxygen supply during the fPDT process by alternatively applying PDT and PTT regulated by two NIR laser beams. Dual-light irradiation can provide more controllability and has recently been widely used in multiple biological and biomedical fields, such as cancer treatment, [21] antibacterial, [40] photopharmacology, [41] optogenetics, [42] and optical-control of protein function and signaling, [43][44][45] etc. Moreover, the replacement of the dark cycle of conventional fPDT with PTT further enhanced the overall outcome of the anticancer phototherapy due to the synergistic effect of PDT and PTT (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%